A longitudinal study of cortical auditory maturation and implications of the short inter-implant delay in children with bilateral sequential cochlear implants - ÇİPRUT, AYŞE AYÇA (My University, 2023)
© 2023 Elsevier B.V.Objective: This longitudinal study aimed to investigate the maturational development of P1 latency and the effects of a short inter-implant delay in children who received bilateral sequential cochlear implants. Materials and methods: Fourteen children (first CI mean age: 1.4 ± 0.4 years and Second CI mean age: 3.3 ± 0.5 years) who had received sequential bilateral cochlear implants during the sensitive period for auditory maturation participated in our study. The speech-evoked cortical P1 response was recorded after the activation of the second CI at four intervals (implant activation, 3 months, 6 months, 12 months) under three listening conditions (first CI, second CI, binaural). Results: Our results showed that the P1 latencies of the second CI reached normative values within 3 months, but did not reach the P1 latency of the first CI until 12 months. We found a strong negative correlation between the inter-implant delay and the P1 latencies of the second CI when the second CI was activated. Conclusion: Changes in cortical auditory responses over time resulted in normal auditory maturation in children with sequential bilateral cochlear implants during the sensitive period. The results also provide evidence that the timing of auditory experience in the first ear during the sensitive period may influence the speed of compensation in children receiving sequential cochlear implants.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KULAK BURUN BOĞAZ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; OTORHINOLARYNGOLOGY; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; Otorhinolaryngology; Bilateral sequential cochlear implantation; Children; Cortical auditory evoked potentials; Cortical auditory maturation; Inter- implant delay